Logistics and Maintenance Support for Vehicles in the Agro-Industrial Complex (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Social Media in Marketing refers to the strategic use of social networking platforms as powerful tools for promoting and enhancing a brand’s visibility, engagement, and overall marketing objectives. This article is about the advantages of utilizing social media in marketing.